Untreated Atypical Left Femoral Shaft Fracture: A Case Report of Its Complication - Aouad, Dany; Azar, Nagham; Daher, Mohammad; Dib, Nabil; El Rassi, Georges (International Journal of Clinical Research, 2023)
Background: Bisphosphonate therapy is used to manage osteoporosis and decrease the risk of vertebral and hip fractures. These drugs act by suppressing osteoclast activity by inducing the inhibition of bone resorption and increasing bone mineral density. It has been shown that long-term use of bisphosphonate is correlated to a higher incidence of atypical femoral fractures. Case report: This is a case report of an 81-year-old female, on bisphosphonate therapy for 12 years and with chronic left thigh pain for two and a half years who developed an incomplete atypical left femur fracture. What’s special about this case is that the fracture was ignored and then progressed after three months into a complete displaced spiral fracture that required surgical fixation. Conclusion: The benefits of bisphosphonate treatment in preventing osteoporotic fractures outweigh the risk of the occurrence of these atypical fractures. Orthopedic surgeons as well as primary care physicians must keep atypical fractures in their differential diagnosis in patients presenting with prodromal symptoms and who are on long-term bisphosphonate therapy